Gugatan Terhadap Negara Dan Korporasi: Analisis Hukum Lingkungan Atas Bencana Hidrometeorologi Sumatera November–Desember 2025 - Zakiyah; Diva Raya Naysila Nada; Zahra Davika Mulyani; Revameila Susanti; Raisa Agnia (Yayasan Al-Afif, 2025)
The hydrometeorological disaster that struck Sumatra in November to December 2025 claiming 1,072 lives and causing material losses of Rp68.67 trillion cannot be viewed merely as a natural phenomenon. This article analyzes the catastrophe as an ecological disaster rooted in the failure of both the state and corporations to uphold environmental sustainability. Using a normative legal research method, the study examines the state’s responsibility in issuing business permits in disaster-prone areas based on principles of good environmental governance, and evaluates the effectiveness of legal remedies through Citizen Lawsuits and Class Actions. The findings reveal systemic violations, including the neglect of Strategic Environmental Assessments (KLHS), spatial planning breaches, and weak oversight of corporate activities in upstream watershed areas, all of which have exceeded ecological carrying and assimilative capacities. In this context, the state may be held accountable for violating citizens’ constitutional rights, while corporations are subject to strict liability and the polluter pays principle. The article recommends strengthening environmental law enforcement through strategic litigation as a pathway to ecological justice and sustainable natural resource governance in Indonesia.